HUMAN RESOURCE MANAGEMENT AT HOSPITAL PROVINCIAL DO NAMIBE – N'GOLA KIMBANDA, ANGOLA - da Caridade Felix Chitanga, Francisca; Malaquias , Celina (Srpski medicinski časopis Lekarske komore, 2025)
Human resource management in the health sector encompasses planning, recruitment, selection, training, career development, performance evaluation, and efforts to enhance the quality of life for workers. However, the sector is facing a crisis due to challenges in human resource management, including workforce shortages, inefficient role distribution, inadequate working conditions, skill gaps, and management strategies that fail to align with the needs of the population. This research aims to analyze human resource management at the Namibe Provincial Hospital “N’Gola Kimbanda” and develop an action plan for its improvement.
Keywords: management; human resources; Hospital Provincial do Namibe; planning